Revisiting reading and writing pedagogies in the ERA of blended learning: A conceptual BRWIM model for EFL contexts - Khan, Nazia; Hassan, Khalid (International Journal of Educational Technology and Learning, 2025)
This article develops the Blended Reading-Writing Integration Model (BRWIM), a comprehensive conceptual framework for enhancing literacy instruction in English-as-a-Foreign-Language (EFL) higher education under blended learning conditions. Reading and writing are often taught as separate skills, and in many low-income and middle-income contexts blended learning policies have focused more on technology adoption than on pedagogy. To address this fragmentation, BRWIM integrates reading and writing as mutually reinforcing literacies and stages them systematically across face-to-face, synchronous online, and asynchronous environments. The model is grounded in established theories of reading (schema, interactive, cognitive) and writing (process-oriented, feedback-focused), and is informed by digital pedagogy frameworks including the Community of Inquiry, TPACK, ICAP, Cognitive Load Theory, and multimedia learning principles. These perspectives are translated into reusable design patterns, rubric-aligned assessments, and orchestration strategies that make BRWIM both evidence-informed and practically implementable. To demonstrate contextual applicability, the paper incorporates authentic indicators from UNESCO, OECD, and national policy reports, alongside illustrative datasets and simplified modelling approaches. These show how instructional design variables, such as pre-class activation, interactive discussions, timely feedback, revision cycles, and cognitive load management, which may influence composite literacy outcomes. The unique contribution of BRWIM lies in consolidating fragmented research into a coherent and operational blueprint. By combining theoretical synthesis, policy alignment, and practice-oriented design tools, the model provides curriculum designers, educators, and institutional leaders with a roadmap for advancing reading-writing development in blended EFL contexts.